High‐Reputation Firms and Their Differential Acquisition Behaviors - Haleblian, Jerayr J.; Pfarrer, Michael D.; Kiley, Jason T. (Strategic Management Journal, 2017)
Research summary: E merging reputation research suggests that high‐reputation firms will act to maintain their reputations in the face of high expectations. Yet, this research remains unclear on how high‐reputation firms do so. We advance this research by exploring three questions related to high‐reputation firms' differential acquisition behaviors: Do high‐reputation firms make more acquisitions than similar firms without this distinction? What kind of acquisitions do they make? How do investors react to high‐reputation firms' differential acquisition behaviors? We find that high‐reputation firms make more acquisitions and more unrelated acquisitions than other firms. Yet, we also find that investors bid down high‐reputation firms' stock more than other firms' in response to acquisition announcements, suggesting that investors are skeptical of how high‐reputation firms maintain their reputations . Managerial summary: W e know that high‐reputation firms wish to maintain their elite standing in the face of high‐market expectations, but we know little about how they do so. We explore this puzzle by investigating how reputation maintenance influences high‐reputation firms' acquisition behaviors. We classify high‐reputation firms are those firms that make Fortune's M ost A dmired annual list, and we find that high‐reputation firms make more acquisitions and more unrelated ones than other firms. Surprisingly, we also find that the market tends to react negatively to these acquisitions. Thus, managers may want to reconsider their strategy of making acquisitions as a means to maintain their firms' high reputations . Copyright © 2017 John Wiley & Sons, Ltd.